2011
DOI: 10.1007/s00299-011-1016-z
|View full text |Cite
|
Sign up to set email alerts
|

Tissue culture-induced flower-color changes in Saintpaulia caused by excision of the transposon inserted in the flavonoid 3′, 5′ hydroxylase (F3′5′H) promoter

Abstract: The variegated Saintpaulia cultivar Thamires (Saintpaulia sp.), which has pink petals with blue splotches, is generally maintained by leaf cuttings. In contrast, tissue culture-derived progeny of the cultivar showed not only a high percentage of mutants with solid-blue petals but also other solid-color variants, which have not been observed from leaf cuttings. Solid-color phenotypes were inherited stably by their progeny from tissue culture. Petals from each solid-color variant were analyzed by high-performanc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
36
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 52 publications
(37 citation statements)
references
References 57 publications
0
36
1
Order By: Relevance
“…The distributions of 3-acetyl-rutinoside-5-glucosides of malvidin, pelargonidin, and peonidin have already been reported in the violet-blue, purple, and pink flowers of S. 'Thamires' as their main anthocyanins (Sato et al, 2011;Tatsuzawa et al, 2012). However, in this study, it was revealed that the red-purple flowers of S. 'Tomoko' contain peonidin 3-acetyl-rutinoside and cyanidin 3-acetyl-rutinoside as the main anthocyanins.…”
Section: -O-[2-o-(β-xylopyranosyl)-6-o-(acetyl)-β-glucopyranoside]contrasting
confidence: 44%
See 1 more Smart Citation
“…The distributions of 3-acetyl-rutinoside-5-glucosides of malvidin, pelargonidin, and peonidin have already been reported in the violet-blue, purple, and pink flowers of S. 'Thamires' as their main anthocyanins (Sato et al, 2011;Tatsuzawa et al, 2012). However, in this study, it was revealed that the red-purple flowers of S. 'Tomoko' contain peonidin 3-acetyl-rutinoside and cyanidin 3-acetyl-rutinoside as the main anthocyanins.…”
Section: -O-[2-o-(β-xylopyranosyl)-6-o-(acetyl)-β-glucopyranoside]contrasting
confidence: 44%
“…However, in this study, it was revealed that the red-purple flowers of S. 'Tomoko' contain peonidin 3-acetyl-rutinoside and cyanidin 3-acetyl-rutinoside as the main anthocyanins. Therefore, it is presumed that S. 'Tomoko' has two characteristic biosynthetic features different from S. 'Thamires' (Sato et al, 2011;Tatsuzawa et al, 2012) for producing the red-purple flowers as follows: (1) it is devoid of flavonoid 3',5'-hydroxylase activity and (2) 5-OH of anthocyanidin is free from glucosylation. On the other hand, anthocyanin in the grayed-purple colored leaves of S. 'Tomoko' contained cyanidin 3-acetylsambubioside as a main anthocyanin.…”
Section: -O-[2-o-(β-xylopyranosyl)-6-o-(acetyl)-β-glucopyranoside]mentioning
confidence: 99%
“…An original research paper by Sato et al (2011) describes how somaclonal variation resulted in higher expression of a flavonoid due to transposon excision from a promoter region.…”
mentioning
confidence: 99%
“…is a suitable model plant to study somaclonal variation because adventitious shoots can easily regenerate from any organ and regeneration from leaves can occur independently of PGR addition. 'Thamires' has pink flowers caused by the pigment pelargonidin with blue splotches due to malvidin (Sato et al, 2011b). The purple variegations result from the deletion of a hAT superfamily TE, VGs1 (Variation Generator of Saintpaulia 1), inserted in the promoter region of flavonoid 3 ',5'-hydroxylase (F3'5'H), such that the transcription of F3'5'H is suppressed by the inactivation of a promoter by the inserted VGs1, belonging to the DNA-mediated TEs (called "class II"), such as Ac/Ds in Zea mays (Müller-Neumann et al, 1984) and Tam3 in Antirrhinum majus (Hehl et al, 1991), resulting in the suppression of malvidin synthesis (Sato et al, 2011b).…”
Section: Introductionmentioning
confidence: 99%
“…The purple variegations result from the deletion of a hAT superfamily TE, VGs1 (Variation Generator of Saintpaulia 1), inserted in the promoter region of flavonoid 3 ',5'-hydroxylase (F3'5'H), such that the transcription of F3'5'H is suppressed by the inactivation of a promoter by the inserted VGs1, belonging to the DNA-mediated TEs (called "class II"), such as Ac/Ds in Zea mays (Müller-Neumann et al, 1984) and Tam3 in Antirrhinum majus (Hehl et al, 1991), resulting in the suppression of malvidin synthesis (Sato et al, 2011b). In previous studies, we determined that the preexisting mutation percentage in the vegetative organ of this cultivar was < 3%, but that the percentages of somaclonal variations induced via adventitious shoots were much higher than 3% (Sato et al, 2011b). This finding indicates that the high levels of somaclonal variation did not occur in mutated but in wild-type cells, and VGs1 was activated in in vitro culture.…”
Section: Introductionmentioning
confidence: 99%